POSSIBILITIES OF APPLICATION OF FOREIGN EXPERIENCE IN THE PROCESS OF MANAGEMENT OF FINANCIAL RESOURCES OF DOMESTIC ENTERPRISES - LOPATOVSKA, Oksana; BOMOK, Anastasiya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article considers the need for the formation and use of financial resources for the need for effective functioning of modern enterprises. The need of domestic enterprises to improve the management of their financial resources is analyzed. It was determined that there are a number of ways of managing the financial resources of economic entities, which make it possible to increase the efficiency of the use of funds. The global practice of modern cash flow management, which is based on such theoretical models as V. Baumol’s model, the Miller-Orr model, B. Stone’s model, and the method of simulation modeling or statistical tests, is studied. It is noted that the successful implementation of cash flow optimization directions at the business level requires appropriate measures to be taken on a national scale as well. Measures are proposed that will contribute to the optimization of cash flows and the activation of entrepreneurship. Special attention is paid to such a way of managing financial resources as planning. It is noted that the world experience of developed countries proves that planning can be replaced by forecasting only in the conditions of a country in which the economy functions successfully and the general economic condition is stable. It is proven that the management of financial resources of French, German and English companies is carried out taking into account certain factors influencing the formation and management of the structure of financial resources of business entities. These factors include the level of financial risk, financial stability, tax burden, and financial management features. It is proven that the management of financial resources of French, German and English companies is carried out taking into account certain factors influencing the formation and management of the structure of financial resources of business entities. These factors include the level of financial risk, financial stability, tax burden, and financial management features.